US Security Policy in South Asia during and after Cold War: An Analysis - Amjad, Salma; Ejaz, Ahmad (Annals of Human and Social Sciences, 2024)
This article is an attempt to analyze the US security policy in South Asia in the Cold War and after end of the Cold War. South Asia has always been important for the US’s strategic objectives in the Asian continent to be advanced. The US’s perception of the threat in Asia has long influenced its policy, which is limited to the construction of security systems there. The main focus of US security strategy in South Asia is maintaining peace and stability in the region. The triangular relationship between the US, Pakistan, and India is actually the main focus of US security policy in South Asia. The United States has consistently reevaluated its South Asian policy in light of its regional security objectives and interests. During the Cold War, Pakistan was seen as the US’s "most allied ally in Asia" because of its perceived threat from the communist growing influence. Pakistan was thus selected to defend US interests in the region. After Cold War, the US’s foreign and security policies were reorganized as a result of the new world order, which turned the world into a unipolar framework. India was chosen as a "natural partner" in the US security strategy for South Asia after it was restructured in light of the US security interests and aims in the Asia-Pacific region, where a new balance of power arrangement has evolved. The 9/11 brought new shift in US and Pakistan relations and both were involved in the fight against terrorism; nevertheless, this "single-issue alliance" is only meant to last temporarily. The research is primarily qualitative in nature. The objective of US policy in the region has always been the security of South Asia as a whole, not simply of one country. India and Pakistan were essential to US goals in the region. Consequently, it wanted to strengthen both states, whether against the Soviet Union or China. The US occasionally modified its security strategy in South Asia to take into account its shifting interests in the region.